2017
DOI: 10.1007/s00280-017-3414-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory growth evaluation and apoptosis induction in MCF-7 cancer cells by new 5-aryl-2-butylthio-1,3,4-oxadiazole derivatives

Abstract: Based on the results of in vitro studies, it could be concluded that compound 5e showed a significant inhibitory growth effect on MCF-7 cells and have the potential to be developed as lead molecule and further structural modifications may result in promising new anticancer agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…DAPI cannot pass through the membrane of live cells very effectively. Due to the condensed nucleus, the apoptotic cells appeared as bright colored on staining with DAPI; this is a distinctive characteristic of apoptosis . Hence, this study distinguishes live cells from apoptotic cells by observing the nuclear morphology to see the effect of 8 k in A‐549 cells.…”
Section: Resultsmentioning
confidence: 96%
“…DAPI cannot pass through the membrane of live cells very effectively. Due to the condensed nucleus, the apoptotic cells appeared as bright colored on staining with DAPI; this is a distinctive characteristic of apoptosis . Hence, this study distinguishes live cells from apoptotic cells by observing the nuclear morphology to see the effect of 8 k in A‐549 cells.…”
Section: Resultsmentioning
confidence: 96%
“…Flow cytometry analysis showed that cancer cells were arrested in the G0/G1 phase of the cell cycle. Western blotting studies (an electrophoresis-based method for the detection of specific proteins [67]) showed high activation of apoptotic protein caspase-3 and decreased expression of antiapoptotic protein Bcl-2 [68].…”
Section: Anti-proliferative Effects Of 134-oxadiazole Derivativesmentioning
confidence: 99%
“…In a previous investigation on 5-aryl-2-butylthio-1, 3, 4-oxadiazole derivatives ( 4a–5f ), we observed antiproliferative effects of these compounds on MCF-7 breast cancer cells as a result of the induction of apoptosis [1]. In the present study, we further explored the potential of these compounds as antioxidants and STAT3 inhibitors through computational analyses to establish the authenticity of these derivatives as potent anticancer agents because antioxidants and STAT3 inhibitors are known to play prominent roles against the progression of cancer.…”
Section: Introductionmentioning
confidence: 77%
“…From previous cytotoxic studies, the IC 50 value for compound 5e was found to be 2.45 ± 1.03 µg/mL for MCF-7 cancer cells [1]. Thus, we investigated the effect of compound 5e on STAT3 in MCF-7 cancer cells at the same concentrations via Western blot assay.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation